COНТИНУИTY OF INNOVATIVE EDUCATIONAL TECHNOLOGIES AND EDUCATIONAL EFFECTIVENESS - Yuldashev Odiljon Toshpulatovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article defines the tasks of providing the educational process with high-quality textbooks and advanced pedagogical technologies, implementing the informatization of the continuous education system. That’s why today’s pedagogue is required not only to be aware of the latest achievements of the educational system, but also to be able to apply them in the course of the lesson. Taking this into account, it is very important to organize practical training lessons in a visual way. Creating virtual exhibitions (stands) allows solving the above problems to a certain extent.